Detection of honey bee viruses in larvae of Vespa orientalis - Power, Karen; Martano, Manuela; Ragusa, Ernesto; Altamura, Gennaro; Maiolino, Paola (Frontiers in Cellular and Infection Microbiology, 2023)
The Oriental hornet (Vespa orientalis) is one of the major predators of honey bees. It has been demonstrated that adults of V. orientalis can harbor honey bee viruses, however the transmission route of infection is still not clear. The aim of this study was to study the possible presence of honey bee viruses in V. orientalis larvae and honey bees collected from the same apiary. Therefore, 29 samples of V. orientalis larvae and 2 pools of honey bee (Apis mellifera). samples were analyzed by multiplex PCR to detect the presence of six honeybee viruses: Acute Bee Paralysis Virus (ABPV), Black Queen Cell Virus (BQCV), Chronic Bee Paralysis Virus (CBPV), Deformed Wing Virus (DWV), Kashmir Bee Virus (KBV) and Sac Brood Virus (SBV). Biomolecular analysis of V. orientalis larvae revealed that DWV was present in 24/29 samples, SBV in 10/29, BQCV in 7/29 samples and ABPV in 5/29 samples, while no sample was found positive for CBPV or KBV. From biomolecular analysis of honey bee samples DWV was the most detected virus, followed by SBV, BQCV, ABPV. No honey bee sample was found positive for CBPV or KBV. Considering the overlapping of positivities between V.orientalis larvae and honey bee samples, and that V.orientalis larvae are fed insect proteins, preferably honey bees, we can suggest the acquisition of viral particles through the ingestion of infected bees. However, future studies are needed to confirm this hypothesis and rule out any other source of infection.